Internalisasi Nilai-Nilai Islam Melalui Media Storybook Berbasis Budaya Lokal “Kisah Kampung Arab Jambi” pada Anak Usia Dini - Fitriah Fitriah; Azwir Azwir; Dina Novitasari Nasution; Efi Fitriani; Maryana Maryana (Tadabbur: Jurnal Integrasi Keilmuan, 2026)
The internalization of Islamic values in early childhood is a fundamental process for developing faith, moral character, and social responsibility as the foundation of lifelong learning; however, learning practices in many Early Childhood Education institutions remain dominated by conventional approaches that provide limited opportunities for children to experience Islamic values in meaningful and contextual ways. Therefore, this study aimed to examine the implementation of a locally based storybook entitled Kisah Kampung Arab Jambi as a medium for internalizing Islamic values among early childhood learners at TK ABA IV Kota Jambi. Employing a qualitative approach with a case study design involving 12 children in Group B, data were collected through classroom observations, semi-structured interviews with teachers, and documentation, and subsequently analyzed using the Miles and Huberman interactive model. The findings revealed that the storybook effectively facilitated the internalization of Islamic values through contextual narratives rooted in local culture, as evidenced by positive behavioral changes among children, including greeting others, praying before and after activities, expressing gratitude, respecting teachers and peers, sharing, helping others, and maintaining environmental cleanliness. Furthermore, the integration of Islamic teachings with the cultural heritage of Kampung Arab Jambi enhanced children's engagement, strengthened their cultural identity, and deepened their understanding of Islamic moral values. This study concludes that culturally responsive storybook media can serve as an innovative pedagogical strategy for strengthening Islamic character education in early childhood settings.